A Narrow and Highly Significant Linkage Signal for Severe Bipolar Disorder in the Chromosome 5q33 Region in Latin American Pedigrees (2009)
ABSTRACT: We previously reported linkage of bipolar disorder to 5q33-q34in families from two closely related population isolates, theCentralValleyofCostaRica(CVCR)andAntioquia,Colombia (CO). Here we present follow up results from fine-scale mapping in large CVCR and CO families segregating severebipolar disorder, BP-I, and in 343 population trios/duos fromCVCR and CO. Employing densely spaced SNPs to fine map theprior linkage peak region increases linkage evidence and clarifiesthe position of the putative BP-I locus. We performed two-pointlinkage analysis with 1134 SNPs in an approximately 9 Mb regionbetween markers D5S410 and D5S422. Combining pedigreesfrom CVCR and CO yields a LOD score of 4.9 at SNP rs10035961.Two other SNPs (rs7721142 and rs1422795) within the same 94kb region also displayed LOD scores greater than 4. This linkagepeak coincides with our prior microsatellite results and suggestsa narrowed BP-I susceptibility regions in these families.To investigate if the locus implicated in the familial form ofBP-I also contributes to disease risk in the population, wefollowed up the family results with association analysis in duoand trio samples, obtaining signals within 2 Mb of the peak linkage signal in the pedigrees; rs12523547 and rs267015(P¼0.00004 and 0.00016, respectively) in the CO sample andrs244960 in the CVCR sample and the combined sample,withP¼0.00032 and 0.00016, respectively. It remains unclearwhether these association results reflect the same locus contri-buting to BP susceptibility within the extended pedigrees.